Application of Projection Pursuit Analysis Method Based on Kernel Function in Fault Diagnosis for Rolling Bearing. Issue 1 (May 2021) - Jing, Cheng; Le, Su; Weiqing, Wang; Shan, He
Abstract: In view of nonlinear and non-Gaussian characteristics of fault feature for rolling bearing of wind turbine, the projection pursuit analysis method based on kernel function is put forward to make pattern recognition for all bearing running states. It elaborates the principle of projection pursuit method, and plan and steps for pattern recognition, then has a simulation and test by MATLAB software. The test results show that the projection pursuit analysis method based on kernel function is an effective method for fault diagnosis, and it can quickly and efficiently identify rolling bearing running states.